Enhanced Weathering Using Basalt Rock Powder: Carbon Sequestration, Co-benefits and Risks in a Mesocosm Study With Solanum tuberosum - Vienne, Arthur; Poblador, Silvia; Portillo-Estrada, Miguel; Hartmann, Jens; Ijiehon, Samuel; Wade, Peter; Vicca, Sara (Frontiers in Climate, 2022)
Enhanced weathering (EW) of silicate rocks can remove CO2 from the atmosphere, while potentially delivering co-benefits for agriculture (e.g. reduced nitrogen losses, increased yields). However, quantification of inorganic carbon sequestration through EW and potential risks in terms of heavy metal contamination have rarely been assessed. Here, we investigate EW in a mesocosm experiment with Solanum tuberosum growing on alkaline soil. Amendment with 50 t basalt/ha significantly increased alkalinity in soil pore water and in the leachate losses, indicating significant basalt weathering. We did not find a significant change in TIC, which was likely because the duration of the experiment (99 days) was too short for carbonate precipitation to become detectable. A 1D reactive transport model (PHREEQC) predicted 0.77 t CO2/ha sequestered over the 99 days of the experiment and 1.83 and 4.48 t CO2/ha after one and five years, respectively. Comparison of experimental and modelled cation pore water Mg concentrations at the onset of this experiment showed a factor three underestimation of Mg concentrations by the model and hence indicates an underestimation of modelled CO2 sequestration. Moreover, pore water Ca concentrations were underestimated, indicating that the calcite precipitation rate was overestimated by this model. Importantly, basalt amendment did not negatively affect potato growth and yield (which even tended to increase), despite increased Al availability in this alkaline soil. Soil and pore water Ni increased upon basalt addition, but Ni levels remained below regulatory environmental quality standards and Ni concentrations in leachates and plant tissues did not increase. Last, basalt amendment significantly decreased nitrogen leaching, indicating the potential for EW to provide benefits for agriculture and for the environment.